Acute Infection of Viral Pathogens and Their Innate Immune Escape - Rai, Kul Raj; Shrestha, Prasha; Yang, Bincai; Chen, Yuhai; Liu, Shasha; Maarouf, Mohamed; Chen, Ji-Long (Frontiers in Microbiology, 2021)
Viral infections can cause rampant diseases in human beings ranging from mild to acute, and often fatal, unless resolved. An acute viral infection is characterized by sudden or rapid onset of disease, which can be resolved shortly by robust innate immune responses exerted by the host or may kill host. Immediately after viral infection, elements of innate immunity such as physical barriers, various phagocytic cells, group of cytokines, interferons (IFNs), and IFN-stimulated genes provide first line of defense for the viral clearance. Innate immunity not only plays a critical role in rapid viral clearance and but can also lead to disease progression by immune-mediated host tissue injury. Although elements of antiviral innate immunity are armed to counter the viral invasion, viruses are evolved with various strategies to escape away from host immune surveillances to establish successful infections. Understanding complex mechanisms underlying interaction between viruses and host innate immune system would help develop rational treatment strategies for acute viral infectious diseases. In this review, we discuss pathogenesis of acute infections caused by viral pathogens and highlight a broad immune escape strategies exhibited by viruses.